2020
DOI: 10.1007/s11757-020-00582-4
|View full text |Cite
|
Sign up to set email alerts
|

Entwicklungspfade der Straftäterbehandlung: skizzierte Wege und Evaluation der Zielerreichung

Abstract: ZusammenfassungDer Aufsatz gibt einen Überblick über die Konzepte und empirischen Evaluationsergebnisse zur Straftäterbehandlung seit den 1960er-Jahren. Zahlreiche Metaanalysen zeigen im Durchschnitt positive Ergebnisse. Kognitiv-verhaltenstherapeutische Programme und das RNR-Modell haben die solideste Evidenzbasis, aber auch einige andere Ansätze sind erfolgversprechend. Bei Sexualtätern sind die Ergebnisse noch weniger einheitlich, insbesondere hinsichtlich der Behandlung in Gefängnissen. Bei der Umsetzung i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 87 publications
0
4
0
1
Order By: Relevance
“…Another six studies ( Abracen et al, 2011 ; Grady et al, 2017 ; Letourneau et al, 2013 ; Olver et al, 2020 ; Smallbone & McHugh, 2010 ; Smid et al, 2016 ) recommended in the Online Supplementary Materials by Schmucker and Lösel (2017) as being eligible for updating their meta-analysis, were also added; again, two of these recommended studies were updated with more recent studies on the same samples ( Grady et al, 2017 ; Olver et al, 2020 ) identified by the current authors. Another two eligible studies ( Buttars et al, 2016 ; Mews et al, 2017 ) were identified based on other recent meta-analyses ( Gannon et al, 2019 ; Lösel, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another six studies ( Abracen et al, 2011 ; Grady et al, 2017 ; Letourneau et al, 2013 ; Olver et al, 2020 ; Smallbone & McHugh, 2010 ; Smid et al, 2016 ) recommended in the Online Supplementary Materials by Schmucker and Lösel (2017) as being eligible for updating their meta-analysis, were also added; again, two of these recommended studies were updated with more recent studies on the same samples ( Grady et al, 2017 ; Olver et al, 2020 ) identified by the current authors. Another two eligible studies ( Buttars et al, 2016 ; Mews et al, 2017 ) were identified based on other recent meta-analyses ( Gannon et al, 2019 ; Lösel, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Treatment of persons who committed sexual offenses focuses on the reduction of sexual recidivism in order to increase public safety. Although previous meta-analyses provided evidence for reductions in sexual recidivism ( Alexander, 1999 ; Aos et al, 2006 ; Furby et al, 1989 ; Gallagher et al, 1999 ; Gannon et al, 2019 ; Grossman et al, 1999 ; Hall, 1995 ; Hanson et al, 2002 , 2009a , 2009b ; Kim et al, 2016 ; Lösel & Schmucker, 2005 ; Mpofu et al, 2018 ; Polizzi et al, 1999 ; Reitzel & Carbonell, 2006 ; Schmucker & Lösel, 2015 , 2017 ; Ter Beek et al, 2018 ; Walker et al, 2004 ), there is still controversy about which sample characteristics, treatment variables, or methodological issues contribute most to the effectiveness of treatment ( Lösel, 2020 ). Sound treatment evaluation in this field is complicated by various concerns, such as the heterogeneity among persons with sexual offense histories in terms of pre-treatment risk of reoffending, variances between adults and juveniles, differences in treatment approaches, and deficits in study design assigning appropriate treatment and control groups ( Lösel & Schmucker, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…In Germany there is a growing interest in prison climate research which has been neglected for a period but is now thought to be a true research desideratum (Guéridon, 2020; Lösel, 2020: 45; Neubacher, 2019: 127). In the past a substantial portion of prison research was dedicated to identifying effective treatment programmes and prisoners well suited to them.…”
Section: Identifying What Matters In Prison Across Bordersmentioning
confidence: 99%
“…The quality of the patient-therapist relationship is as relevant to the treatment effect as the chosen treatment approach. Accordingly, in prison the relational skills of the staff are associated with positive results (Lösel, 2020: 45 with reference to Gendreau et al, 1999). By now, international prison research deems prison climate to be an important, if not the key, parameter of prison life.…”
Section: Identifying What Matters In Prison Across Bordersmentioning
confidence: 99%
“…B. Lösel 2018Lösel , 2020Lösel et al 2019) gibt es demnach sowohl kontraintentionale als auch nonintentionale Wirkungen und Nebenwirkungen -erwünschte wie unerwünschte.…”
unclassified